2016
DOI: 10.1002/pros.23154
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing peptide receptor (GRPr) promotes EMT, growth, and invasion in canine prostate cancer

Abstract: BACKGROUND The gastrin-releasing peptide receptor (GRPr) is upregulated in early and late-stage human prostate cancer (PCa) and other solid tumors of the mammary gland, lung, head and neck, colon, uterus, ovary, and kidney. However, little is known about its role in prostate cancer. This study examined the effects of a heterologous GRPr agonist, bombesin (BBN), on growth, motility, morphology, gene expression, and tumor phenotype of an osteoblastic canine prostate cancer cell line (Ace-1) in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…20 receptor on their surfaces and the receptor functioned biologically as a growth factor, grew reliably in nude mice, and could be optically imaged in vivo and microscopically with IR800-G-Abz4-t-BBN. [12][13][14] The histopathology results reported herein definitively demonstrate the growth of these cells in the prostate glands and other tissues of immunosuppressed dogs, as well as the cells' ability to seed to regional lymph nodes. The new canine model reported herein is thus the first time a human cancer growth factor expressing cell has been grown in dogs.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…20 receptor on their surfaces and the receptor functioned biologically as a growth factor, grew reliably in nude mice, and could be optically imaged in vivo and microscopically with IR800-G-Abz4-t-BBN. [12][13][14] The histopathology results reported herein definitively demonstrate the growth of these cells in the prostate glands and other tissues of immunosuppressed dogs, as well as the cells' ability to seed to regional lymph nodes. The new canine model reported herein is thus the first time a human cancer growth factor expressing cell has been grown in dogs.…”
Section: Discussionsupporting
confidence: 57%
“…Starting with a known isolated Ace‐1 canine prostate cancer cell line that expresses very little mRNA for GRPr and does not bind GRPr targeting peptides, our prior study demonstrated that the Ace‐1 cell line could be transfected with human GRPr. The resulting Ace‐1 huGRPr cells expressed the GRPr receptor on their surfaces and the receptor functioned biologically as a growth factor, grew reliably in nude mice, and could be optically imaged in vivo and microscopically with IR800‐G‐Abz4‐t‐BBN . The histopathology results reported herein definitively demonstrate the growth of these cells in the prostate glands and other tissues of immunosuppressed dogs, as well as the cells’ ability to seed to regional lymph nodes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Canine bombesin peptides show high sequence homology with human and terminate in the same sequence [47], suggesting that the canine Ace-1 cell line expresses few GRPr. In addition, quantitative RT-PCR showed that the Ace-1 cells had very low levels of canine GRPr mRNA in contrast to the primary carcinoma tissues from which the Ace-1 were derived, which had abundant GRPr mRNA [48]. Stable transfection generated 10 canine Ace-1 clones with the plasmid containing human GRPr (Ace-1 huGRPr ), and eight clones with the empty vector (Ace-1 CMV ).…”
Section: Characterization Of Grpr Expression In Ace-1 Cellsmentioning
confidence: 99%